Možnosti in priložnosti tehnološke podpore pri oskrbi ljudi z demenco v skupnosti - Mali, Jana (Kakovostna starost, 2016)
Dementia is becoming increasingly phenomenon in old age, wich affects not only the older people, but also relatives and other people in their social network. The effects of dementia are preventing people with dementia to live completely independently and without assistance due to lack of diversified forms of care or its great pretension. Therefore placing people with dementia in homes for older people is very common practice. In order to preserve and protect the indipendence of people with dementia and strive to minimize the subsequent departure of people with dementia in the institution, in this paper we show an overview of exsisting technology as a complement to human care in the community. We present how to research the need of people and based on their living conditions and the degree of dementia, create technology solutions to address the specific obstacles and risks in everyday life of people with dementia. The introduction of information and communication technology in long-term care for people with dementia should be based on an interdisciplinary search for solutions and participation of people with dementia. It is important to take into account the previous experience of people with dementia in the use of technological solutions in everyday life based on the abilities of people with dementia.
Keywords: demenca; dementia; celostna oskrba; dolgotrajna oskrba; social work; socialno delo; informacijsko-komunikacijska tehnologija; information and communications technology; stari ljudje